The concise book of neuromuscular therapy : a trigger point manual - Sharkey, John. (Berkeley, Calif. : North Atlantic Books, 2008)
'A manual teaching the techniques of neuromuscular therapy (NMT), and how to combine it with medical exercise interventions, for the treatment of soft tissue pain and injury'--Provided by publisher.
Includes bibliographical references (p. [229]) and indexes.
Keywords: Manipulation (Therapeutics).; Soft tissues injuries -- Chiropractic treatment; Soft tissues injuries -- Exercise therapy